Sistem Informasi Penerimaan Beasiswa KIPK Mahasiswa Institut Karya Mulia Bangsa (IKMB) Berbasis Website - Rudi Hermawan; Supatman Supatman (Jurnal Kridatama Sains dan Teknologi, 2026)
Scholarships are financial assistance awarded to support education, typically to students with academic achievements and those from economically disadvantaged backgrounds. This program aims to improve educational accessibility and ensure continuity of learning opportunities. The Karya Mulia Bangsa Institute (IKMB) has established a scholarship program for outstanding students as part of efforts to enhance human resource quality in Semarang Regency. However, the dissemination of scholarship information remains limited, making it difficult for students to obtain timely, accurate information on registration procedures. This study aims to develop a web-based scholarship information system that integrates infographic technology to enhance information accessibility and presentation. The system development approach is implemented in the IKMB campus environment as the research site and data collection location. The developed system is expected to provide structured, interactive, and easily accessible scholarship information for students. The results indicate that the developed information system can facilitate students in accessing scholarship information and completing online registration processes without the need to visit the registration site directly. Therefore, this system contributes to improving the effectiveness of information dissemination and the efficiency of scholarship administrative processes within IKMB